Language, identity, and ideology: Analysing discourse in Aceh sharia law implementation - Habiburrahim, H.; Rahmiati, Zainah; Muluk, Safrul; Akmal, Saiful; Aziz, Zulfadli A. (Universitas Pendidikan Indonesia, 2020)
The implementation of Sharia law in Aceh in 2001 has ignited various reactions from both national and international communities. Some argued that this Sharia law could have a detrimental effect on human rights issues. Others claimed that as a province populated by the Muslim majority, Aceh should be given an opportunity to legalise its own legal product, ensuring that Sharia law is part of Acehnese religious values. This paper is primarily concerned with analysing the texts taken from The Jakarta Post newspaper’s article regarding the formal implementation of the local Sharia law in Aceh. The article is examined by means of various tools in Discourse Analysis method, including social identity, speech acts and implicature, genres and register. The findings elucidate that the speech and discourse of the participants and their interpretation are highly influenced by identity and community ideology of the speakers.